Organisational influences on attitudes in mandatory system use environments: a longitudinal study. (19th July 2005) - Ward, Kerry W.; Brown, Susan A.; Massey, Anne P.
Usage of information systems has moved increasingly from being an optional means of enhancing productivity to a required part of organisational jobs. However, prior research on technology acceptance has largely focused on volitional systems and on individual rather than organisational factors that could influence technology acceptance and use. As a result, little is known about how management may be able to influence user attitudes toward use of mandatory systems. In this paper, we examine the impact of organisational level influences on individual user attitudes toward system use over time. Our study is set in the context of a major mandatory system implementation at a multi-bank holding company. Our results suggest that subjective norms, top management commitment, and perceived organisational benefits are important to users at different times in the implementation process. Our results also highlight that direct system experience plays a significant role in determining which factors are important and when.